Faktor Kecemasan Terhadap Ujian pada Mahasiswa - Azzahra Fadhilla Amelia; Oktafany Oktafany; Shinta Nareswari; Oktadoni Saputra (Medula, 2026)
Test anxiety is a common psychological condition experienced by university students and can negatively affect academic performance and psychological well-being. This study aimed to examine the causes, manifestations, and impacts of test anxiety among students through a literature review approach. Relevant literature was obtained from Google Scholar and national and international scientific databases using the keywords “test anxiety,” “exam anxiety,” “students,” and “academic performance.” A total of 23 articles published between 2010 and 2025 met the inclusion criteria and were analyzed narratively. The findings revealed that test anxiety is influenced by various factors, including academic demands, social pressures, individual characteristics, and learning environment conditions. One of the reviewed studies by Bhuwana (2025) reported that 98.5% of students (197 of 200 respondents) experienced anxiety during the Objective Structured Clinical Examination (OSCE), with the primary causes being limited examination time (21%), the large amount of material to be studied (20.5%), and difficulties maintaining concentration or experiencing forgetfulness during examinations (19.5%). Manifestations of test anxiety include physical, cognitive, and behavioral symptoms such as increased heart rate, excessive worry, negative thoughts, impaired concentration, and procrastination. These symptoms may contribute to lower academic achievement, reduced learning motivation, increased stress levels, and emotional exhaustion. Therefore, effective stress management strategies and institutional support are essential to help students cope with examination-related stress, improve academic performance, and maintain psychological well-being through supportive learning environments and accessible counseling services.